INNV-14. PROSPECTIVE SURGICAL STUDY ON THE FEASIBILITY OF SEMI-AUTOMATED TISSUE COLLECTION, STABILIZATION, PRESERVATION, AND SITE TRANSFER IN GLIOBLASTOMA - IMPROVING UNDERSTANDING OF IMMUNE LANDSCAPE OF TUMOR. (14th November 2022) - Mohammadi, Alireza; Grabowski, Matthew; Watson, Dionysios; Lauko, Adam; Lathia, Justin; Ahluwalia, Manmeet
Abstract: INTRODUCTION: Despite advances in targeted therapy and immunotherapy of many cancers, glioblastoma outcome is still suboptimal in part due to heterogeneity of tumor. Standard surgical approach for glioblastoma is to remove the enhancing tumor and adjuvant treatment used to treat residual infiltrative tumor in non-enhancing surgical wall. We evaluated samples from both areas using advanced techniques of intraoperative resecting, collecting and biologically preserving viable fresh tissue for evaluation of immune landscape and special genomics of tumor. METHODS: 20 patients with glioblastoma enrolled in the study. Before removal of tumor, 3 different samples from central core, enhancing rim and non-enhancing portion of tumor were obtained using navigation assisted NICO Myriad. Fresh tissue was collected separately by an intraopertive Automated Tissue Preservation System (ATPS) and promptly prepare in iced-cold container for laboratory evaluation of tumor tissue viability, bio-banking and flow-cytometric analysis. RESULTS: Average age was 65 years-old and 11 patients were female (55%). No adverse event was observed and on average, sampling added 10 minutes to surgical time. Flow-cytometry showed that non-enhancing portion of glioblastoma compared to enhancing tumor has less immune cells and different abundance of multiple subsets including lower CD8:CD4 ratio and more abundant of CD4 memory T-cells. However there remain activated/exhausted T-cells and suppressive myeloid cells in the non-enhancing tumor. Tissue is sent for micro-RNA analysis and next-generation sequencing as well. CONCLUSION: Taken together, navigation assisted sampling and semi-automated tissue collection, stabilization, and preservation using ATPS is a safe and feasible technique to obtain viable cells for evaluation of heterogeneity of glioblastoma, especially for non-enhancing portion of tumor. This information can be used developing next-generation therapy. Initial results of flow-cytometry showed overall decreased leukocyte infiltration, with underrepresentation of selected immune cell subsets in non-enhancing tumor compared to enhancing portion. Further studies regarding micro-RNA analysis and next-generation sequencing are underway.